Marine macroalgae as an alternative in the feeding of broiler quails in an environment of thermal stress - Oliveira, Airton Gonçalves de; Furtado, Dermeval Araújo; Ribeiro, Neila Lidiany; Marques, Jordânio Inácio; Leite, Patrício Gomes; Mascarenhas, Nágela Maria Henrique; Silva, Ricardo de Sousa; Dornelas, Karoline Carvalho; Rodrigues, Raimundo Calixto Martins; Brito, Alícia Nayana dos Santos Lima de; Lima, Vitória Régia do Nascimento; Chiodi, John Edson (Food Science and Technology, 2023)
The objective of this research was to evaluate the productive performance, carcass quality, and intestinal biometry of European quails (Coturnix coturnix coturnix), kept under cyclic heat stress (air temperature of 32.5°C±0.5) receiving a ration with different concentrations (0, 2.5, 5, and 7.5%) of seaweed meal of Sargassum sp. A total of 240 quails were used, distributed in a completely randomized design with 4 levels of bran inclusion, 6 replications, and 10 birds per experimental unit. An analysis of variance (ANOVA) was performed, and the means were compared by Tukey's test with 5% probability and subjected to regression by PROC REG of SAS® (2002). No similarity was observed in water and feed consumption between treatments. There was a significant difference in most of the variables studied, with a significant difference only occurring in the dorsum, gizzard, and large intestine. Therefore, it is recommended to include up to 7.5% of sargassum bran in the diet of European quails kept under a 12-h heat cycle (32°C±0.5).